Pengaruh pemanfaatan artificial intelligence (AI) terhadap motivasi belajar mahasiswa dengan literasi digital sebagai variabel moderating - Tasya, Cindy Hanna; Sangka, Khresna Bayu; Octoria, Dini (Jurnal Pendidikan Ekonomi (JUPE), 2025)
This study aims to examine the influence of artificial intelligence (AI) utilization on the learning motivation of Economic Education students at Universitas Sebelas Maret (classes of 2021–2022), with digital literacy as a moderating variable. A quantitative approach using a survey method was applied. A total of 160 students were selected from a population of 255 using proportionate random sampling. Data were collected through an online questionnaire and analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that AI utilization has a positive and significant effect on learning motivation. Furthermore, digital literacy functions as a negative moderator in the relationship; students with higher levels of digital literacy experience less impact of AI on their motivation. These findings highlight the importance of strengthening students’ digital literacy to ensure the effective and ethical use of AI in educational settings. The study recommends institutional policies that support training and mentoring programs aimed at enhancing both digital literacy and the responsible integration of AI in higher education environments.